17 - PULMONARY AUSCULTATION – A MULTIPROFESSIONAL ANALYSIS (Fiep Bulletin - online, 2011)
Pulmonary auscultation is an important evaluation instrument of pulmonary functions; it presents the advantage of being a low cost instrument and of easy applicability. Generally auscultation sounds differ from occupations that use it as diagnostic technique. Objective: to make a bibliography review in health area to see if it shows any differences in pulmonary auscultation between experts in health care area. Methodology: it was made a descriptive study, based on bibliography data of studies published from January 1980 to December 2008. It was selected national and international periodic articles, available in the databases of PubMed, LILACS (Latin American and Caribbean Health Sciences), SciELO (Scientific Electronic Library Online), the directory CAPES and quotes from books obtained at Faculdade Assis Gurgacz FAG, in Cascavel city, Parana state, during the period from August to October 2009. The data collection had aimed to select scientific articles analyzing them not irrespective of its title and abstract from all articles published to select the potential articles. The articles selected for the survey had as inclusion criteria: to present title "pulmonary auscultation", sequence points from auscultation, pulmonary auscultation diagnosis, English and Portuguese essay and be available in electronic format, books, besides including one of the keywords in the research. It was found 26 items entirety available. It was included 08 articles and 03 chapters' book that fit the inclusion criteria. Results: the lack of translation knowledge of new terms describing pulmonary sounds about adventitious noises end up becoming responsible for the lack of nomenclature standardization, making it difficult to communicate in medical practice and education. Conclusion: The inappropriate terms used in the evaluation from pulmonary auscultation, keeps being results from imprecise evaluation among professionals in health area.
Keywords: pulmonary auscultation; pulmonary sounds; auscultation of pulmonary sounds